Pengajaran Kitab di Pesantren - Taufiqurrahman, Taufiqurrahman; Prasetyo, Dony Agus; Fahmi, Putri Firdaus; Aula, Fitria Faradina Kafa; Fatimah, Siti (TSAQOFAH, 2026)
This study examines the concepts, methods, and contemporary relevance of teaching classical kitab texts in Indonesian pesantren. Guided by three research questions—concerning the definition of kitab instruction, the methods used in the teaching process, and the challenges encountered in the modern era. The study aims to describe the practice of kitab teaching and analyse its position and continuity in the present context. Using a qualitative descriptive approach, the research finds that kitab instruction is a systematic process of guiding santri to understand authoritative texts through traditional methods such as bandongan, sorogan, and halaqah. These methods strengthen text comprehension, develop interpretive competence, and cultivate disciplined learning grounded in respect for teachers and scholarly traditions. The study also identifies several contemporary challenges, including digital distractions, shifting learning preferences, and the need for more adaptive pedagogical strategies. Nevertheless, kitab teaching remains relevant due to its integrative role in shaping the intellectual, spiritual, and moral character of santri, thereby reaffirming pesantren as a key pillar of Islamic education.